APPLICATION OF COMPUTER VISION TECHNOLOGIES FOR AUTONOMOUS PILE MANIPULATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Modern robots can perform uncreative monotonous tasks. One of such tasks is pile manipulation. Computer vision technologies can help robots acquire additional information by analyzing a pile of complex objects. One of such complex objects is a fish. The presented work investigates the problems of complex object analysis using computer vision. This paper addresses the challenges of image pre-processing, image segmentation, fish detection and occlusion detection. This work results can be useful for developing a computer vision system for pile manipulation.